An examination of the long-term relationship between hydrologic variables and summer algal biomass in a large Prairie reservoir. Issue 1 (2nd January 2019) - Abirhire, Oghenemise; Hunter, Kristine; Davies, John-Mark; Guo, Xulin; de Boer, Dirk; Hudson, Jeff
Abstract: Hydrological drought as characterized by low river inflow rate (IR), and, in turn, low water level (WL) and greater water residence time (WRT), may support greater algal biomass and blooms in lakes. Lake Diefenbaker (LD), a large mesotrophic reservoir on the Canadian Prairies, receives ∼98% of its inflow from the South Saskatchewan River (SSR). The SSR annual flow volume largely varies with precipitation and temperature in the Rocky Mountains. The SSR basin has experienced multiple years of hydrological drought. To test the hypothesis that periods of lower inflows are related to increased algal biomass in LD, summer chlorophyll- a was related to hydrologic variables (IR, WL and WRT). A 31-year period of hydrologic data and estimated chlorophyll- a (i.e. derived from Landsat imagery) was examined. Summer chlorophyll -a ranged from 3.8 to 7.6 μg/L, and late spring and early summer IR, WL and WRT were 117–1061 m 3 /s, 550.7–556.2 m and 0.3–2.1 years, respectively. Chlorophyll- a increased as WL decreased in LD (R 2 adj = 0.30, P = 0.00081). This inverse relationship may be a function of light penetration and internal nutrient loading. Chlorophyll- a had a weak, inverse relationship with IR (R 2 adj = 0.12, P = 0.0315) that was likely driven by an extreme high-flow event. Chlorophyll- a was not significantly related to WRT (R 2 adj = 0.06, P = 0.1), which may be due to the limited variability in WRT and the size of LD. It was hypothesized that a water volume reduction exceeding 25%, caused by water abstraction or drought, or both, may support greater algal biomass in LD. Such reductions are unusual in the historical record, but will likely become more common with frequent drought together with water abstraction in the SSR basin as the Prairies continue to warm.